Migrant Image as an "Other Some" in the Russian Mass Media - Bakanov, Roman P.; Egorova, Lilia G.; Tumanov, Dmitriy V. (Journal of History Culture and Art Research, 2017)
This article reveals the main approaches and methods of forming a perception stereotype of the migrant image as "other some" in the Russian mass media. The authors of this article analyzed three federal print publications - "Rossiyskaya Gazeta", "Trud" and "Komsomolskaya Pravda", characterized as mass editions, which enabled to make the most complete coverage of several segments of the readership and to highlight the most widespread meaning of the "migrant" concept in the public consciousness. The study of the dynamics of using the "migrant" concept for the period of 2000-2013 in the Russian print media made it possible to conclude that there were shifts towards a positive assessment of "other some". If the "language of enmity" was used in the public consciousness to form the migrant image at the beginning of the period under investigation, which led to the consolidation of migrant phobia, then the situation changed by 2013 - the migrant image was more often associated with a victim of interethnic tension and corruption. The new migrant image is the image of a migrant who has not found a better life, but has adopted Russia as a second home and therefore trying to adopt new standards and living conditions and helping to solve many of the social and economic problems of Russian society.